2014
DOI: 10.1021/ja501745g
|View full text |Cite
|
Sign up to set email alerts
|

A Robust and Versatile Photoinduced Living Polymerization of Conjugated and Unconjugated Monomers and Its Oxygen Tolerance

Abstract: Controlled/living radical polymerization techniques have transformed polymer chemistry in the last few decades, affording the production of polymers with precise control over both molecular weights and architectures. It is now possible to synthesize almost an infinite variety of macromolecules using nonspecialized equipment, finding applications in high-tech industry. However, they have several shortcomings. Until recently, living radical polymerizations could not be controlled by an external stimulus, such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

17
897
3
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 882 publications
(932 citation statements)
references
References 82 publications
17
897
3
2
Order By: Relevance
“…Other examples of photo enabled CRPs of other monomers have also recently been reported [57,58]. Moreover, we have also shown that while the concentration of PVDFACH 2 ACF 2 AI chain end decreases and that of PVDFACF 2 ACH 2 AI chain end increases with conversion, their sum, the total iodine chain end functionality, remains relatively constant, and >90%, a value suitable for block copolymer synthesis.…”
supporting
confidence: 79%
“…Other examples of photo enabled CRPs of other monomers have also recently been reported [57,58]. Moreover, we have also shown that while the concentration of PVDFACH 2 ACF 2 AI chain end decreases and that of PVDFACF 2 ACH 2 AI chain end increases with conversion, their sum, the total iodine chain end functionality, remains relatively constant, and >90%, a value suitable for block copolymer synthesis.…”
supporting
confidence: 79%
“…Recently, many new photoinitiating systems for controlled polymerization with visible light, and even sunlight, have been reported (see Table 13) [20,21,[246][247][248][249][250][251][252][253][254][255]. These systems are mainly based on the photoinduced ATRP and/or the photoredox catalysis approach [20,21,[248][249][250][251][252][253][254][255].…”
Section: Controlled Radical Polymerization Upon Soft Visible Lightmentioning
confidence: 99%
“…These systems are mainly based on the photoinduced ATRP and/or the photoredox catalysis approach [20,21,[248][249][250][251][252][253][254][255]. The use of Cu or Ir catalysts has been found particularly appropriate, i.e., these compounds exhibit excellent visible light absorption properties.…”
Section: Controlled Radical Polymerization Upon Soft Visible Lightmentioning
confidence: 99%
“…24 In addition, Xu and coworkers reported a new photoinduced living polymerization involving an electron transfer process between fac-Ir(ppy) 3 and the thiocarbonylthio compound and a cooperative RAFT process that would be able to polymerize a large range of monomers, even in the presence of oxygen. 25,26 Futhermore, the facIr(ppy) 3 catalyst has also been exploited in the surface grafting polymerization [27][28][29] and post-functionalization of polymers. 29,30 As a summary, fac-Ir(ppy) 3 has been successfully used in organic chemistry, polymer modification and materials science without the addition of sacrifice reductants.…”
mentioning
confidence: 99%